ADHD and Adolescent Athletes - Nazeer, Ahsan; Mansour, Miriam; Gross, Kathleen A. (Frontiers in Public Health, 2014)
Attention Deficit Hyperactivity Disorder (ADHD) is a common neurodevelopmental disorder that affects the child and adolescent population. It affects attention span and impairment in concentration, which can impact performance of athletes. Attention deficit hyperactivity disorder (ADHD) treatment within the athletic population is a unique challenge. The research in this field has been relatively limited. The national collegiate athletic association (NCAA) and International Olympic Committee have regulations for the use of psychostimulants for treatment due to its performance enhancing effects. In this article authors have discussed the screening methods, pharmacological treatment, side effects and behavioral approaches for the treatment of ADHD in adolescent athletes